PERBEDAAN KETERAMPILAN BERBAHASA PRODUKTIF MAHASISWA DITINJAU DARI MODEL PEMBELAJARAN BRAIN DAN INVESTIGASI KELOMPOK - Andri Pitoyo (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2020)
Coourse learning outcome (CPMK) provide clear direction for the learning process. In addition, it provides a real picture of actions and teaching and learning behavior for univercity students and lecturs.The learning processes and events that are interesting, fun, innovative, and creative will have a positive effec on the echievement of learning objectives. The statement indirectly requires lectures to design and implement intesting learning models. Facts in the fieldshow that there are many learning models applied by lecturers that are not in accordance with the specified learning outcomes. The learning achievement of produktive language skills (KBP) requires univercity students to be able to produce scientific papers are published in the form of academic seminars. This demand has implications for the teacher's obligation to prepare an interesting, effective, and fun learning model. The purpose of this study was to determine the effect of the BRAIN learning model on Productive Language Skills. This research was conducted at the Nusantara PGRI Kediri University in the odd semester of the 2019/2020 academic year with a sample of 62 students. The group was divided into 2 namely experiment and control. The experimental group used the BRAIN model and the control class used the Group Investigation model. The results showed that there were differences in the average language skills of students between the experimental class and the control class. If viewed from the KBP, the experimental class has an average value of 65.29 which is better than the control class of 63.88.